Peran Pengawas Menelan Obat dalam Penanggulangan Tuberkulosis di Wilayah Kerja Dinas Kesehatan Kota Pekanbaru - Dwi Sapta Aryantiningsih; Ambiyar Ambiyar; Dedy Irfan (Jurnal Kesehatan Komunitas, 2020)
Tuberculosis (TB) is one of the 10 infectious diseases that can cause mortality worldwide. Geographically, the highest TB cases occurred in Southeast Asia (44%). Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Indonesia is among the 3 countries that account for two-thirds of TB cases in the world is 8%. The case finding rate in Riau Province was only 39% and in Pekanbaru City it was only 37.5%. The cure rate for TB patients in Indonesia reaches 73.2% and in Pekanbaru it is only 59.9%, which is still below the Ministry of Health's target of 85%. Family support is very important to observe patient reports for regular medication during the treatment period until it recovers. This study aims to see the role of family support in TB control efforts. Type of qualitative research. The research subjects were 1 holder of the TB Health Office program, 1 staff, 2 Puskesmas program holders, 2 family. Data collection was carried out by interview and document search. The results showed that the family support involved was the patient's family. Health workers provide health information to family related to modes of transmission, how to take TB drugs, schedule patient re-visits. The role of family support is still needed to be improved to support TB treatment. It is recommended to use information systems such as SMS, Web or YouTube to increase the role of family support and patient compliance to follow TB treatment procedures. Keywords: Family support, drug, Tuberculosis